Cranberry Supplement, D-Mannose, and Other OTC Modalities for Prevention of Recurrent UTI in Women Post-Electrofulguration - Kenee PRM; Christie AL; Zimmern PE (Dove Medical Press, 2022)
Parker RM Kenee,1 Alana L Christie,2 Philippe E Zimmern1 1Department of Urology, UT Southwestern Medical Center, Dallas, TX, 75290-9110, USA; 2Simmons Comprehensive Cancer Center Biostatistics, UT Southwestern Medical Center, Dallas, TX, 75390-8852, USACorrespondence: Philippe E Zimmern, Department of Urology, UT Southwestern Medical Center, 5323 Harry Hines Blvd, Dallas, TX, 75390-9110, USA, Tel +1 214 648 9397, Fax +1 214 648 8786, Email Philippe.Zimmern@UTSouthwestern.eduPurpose: To assess patient reliance on various over-the-counter (OTC) modalities used for prevention of recurrent urinary tract infection (RUTI) after electrofulguration (EF).Patients and Methods: Following IRB approval, qualifying women were offered a short survey over the phone by a medical researcher to collect information about their use of various OTC modalities for prophylaxis of RUTI. Data was compared between two cohorts, ≥ 70 years old and < 70 years old, using chi-squared and Student's t-tests.Results: From a database of 324 patients, 163 accepted the interview. 17% (28/163) reported current use of cranberry supplements, 10% (16/163) D-mannose supplements, and 42% (69/163) another non-prescription modality for RUTI prophylaxis. The non-geriatric (< 70 years old) cohort spent, on average, $80 less annually on cranberry/D-mannose supplements (P=0.043) than the geriatric cohort and were more likely to use non-prescription modalities for the prevention of UTI (52% vs 30%; P=0.0061). Individuals using D-mannose were also much more likely to purchase their product online compared to those using cranberry supplements (85% vs 56%). Across all modalities, the perceived benefit difference in reducing UTI/year ranged from a median of 0 for Pyridium® (phenazopyridine hydrochloride) to four for probiotics, with D-mannose and cranberry at two/year, and those increasing daily fluid consumption at 2.5 fewer UTI/year.Conclusion: Continued use of non-prescription modalities for RUTI prophylaxis were common among women with an EF history, but varied based on age groups. Across both age cohorts, annual expenditure and perceived benefit also varied among different OTC prophylactic modalities. Awareness of type and method of OTC modality implementation by patients with RUTI is essential to aligning use with current field recommendations.Keywords: recurrent UTI, menopausal women, cranberry, D-mannose, UTI supplements